Analisis Implementasi Fungsi Manajemen dan Kaitannya dengan Peningkatan Pelayanan pada Calon Jamaah Haji Kantor Kementerian Agama Kabupaten Pasaman - Faradila Faradila; Jon Kenedi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The implementation of service satisfaction from the Pasaman Regency Ministry of Religion for prospective Hajj pilgrims as well as the use of the Integrated Hajj Computerized System (SISKOHAT) in assigning employees based on their Hajj expertise was the driving force for this research. This research used a qualitative descriptive approach and was conducted in the field. Interviews and observations were used as data collection methods. Employees of the Hajj Organizing Section of the Pasaman Regency Ministry of Religion Office became research informants. The Pasaman Regency Ministry of Religion Office has carried out guidance, training and guidance to improve the quality of service for prospective Hajj pilgrims, in accordance with research findings and analysis of the implementation of management functions and their relationship with improving services for prospective pilgrims. Hajj. This service improvement is carried out in accordance with the regulations of the Ministry of Religion office as well as the theory and practice of coaching led by the leadership. Managerial tasks in the form of organizing, planning, implementing and controlling are also carried out by this office.